TIPE KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL-SOAL GEOMETRI BERDASAR NEWMAN’S ERROR ANALYSIS (NEA) - Anita Dewi Utami (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
The students' ability to solve mathematical problems are affected directly or indirectly by their pattern of problem solving when they were attending primary and secondary schools. The result of observation shows that there are students who can not answer proving problem and take no action at all, thoughit is only at the step of understanding the problem. NEA is a frame work with simple diagnostic procedures, which include (1) decoding, (2) comprehension, (3) transformation, (4) process skills, and (5) encoding. Newman’s developed diagnostic method is used to identify the error categories of descriptive test answer. Therefore, the descriptive types of students’ error in proving problem solving in Geometry 1 subject based on Newman’s error Analysis (NEA), and what are the causes for the student’s mistakes in solving those proving problem, especially in Geometry1 subject is interesting to be discussed in this article.